Ciudadanos precarios. Naturalización y extranjería en el México decimonónico - Pani, Erika (El Colegio de México, A.C., 2012)
This research analyzes the laws regarding naturalization and foreigners that were put into force during the nineteenth century, in order to explore how the political community's borders were defined and how the processes for becoming part of this community were established and regulated. Such legal and administrative devices become privileged viewpoints from which to analyze the limits and reaches of State consolidation in nineteenth-century Mexico.